Gardenia Decoction Prevent Intestinal Mucosal Injury by Inhibiting Pro-inflammatory Cytokines and NF-κB Signaling - Yizhe Cui; Qiuju Wang; Mengzhu Wang; Junfeng Jia; Rui Wu (Frontiers Media S.A., 2019)
Gardenia jasminoides Ellis, which belongs to the Rubiaceae family, is a widely used traditional Chinese medicine. Although effect of Gardenia jasminoides Ellis has been widely reported, its anti-inflammatory role in intestinal mucosal injury induced by LPS remains unclear. In the present study, we investigated the effects of decoction extracted from Gardenia jasminoides on the morphology and intestinal antioxidant capacity of duodenum induced by LPS in mice. Further analysis was carried out in the expression of inflammatory and anti-inflammatory cytokines. Nuclear factor-kappa B (NF-κB) was determined by Western blot. Gardenia jasminoides water extract was qualitative analyzed by high-performance liquid chromatography coupled with electro spray ionization quadrupole time-of-flight mass spectrometry. The results showed that Gardenia decoction markedly inhibited the LPS-induced Tumor necrosis factor (TNF)-α, Interleukin (IL)-6, IL-8, and IL-1 production. It was also observed that Gardenia decoction attenuated duodenum histopathology changes in the mouse models. Furthermore, Gardenia decoction inhibited the expression of NF-κB in LPS stimulated mouse duodenum. These results suggest that Gardenia decoction exerts an anti-inflammatory and antioxidant property by up-regulating the activities of the total antioxidant capacity (T-AOC), the total superoxide dismutase (T-SOD), and glutathione peroxidase (GSH-Px). Gardenia decoction is highly effective in inhibiting intestinal mucosal damage and may be a promising potential therapeutic reagent for intestinal mucosal damage treatment.